Screening and Evaluation of Streptomyces Species as a Potential Biocontrol Agent against a Wood Decay Fungus, Gloeophyllum trabeum. Issue 2 (3rd April 2018) - Jung, Su Jung; Kim, Nam Kyu; Lee, Dong-Hyeon; Hong, Soon Il; Lee, Jong Kyu
Abstract: Two-hundred and fifty-five strains of actinomycetes isolated from soil samples were screened for their antagonistic activities against four well-known wood decay fungi (WDF), including a brown rot fungus, Gloeophyllum trabeum and three white rot fungi Donkioporia expansa, Trametes versicolor, and Schizophyllum commune . A dual culture assay using culture media supplemented with heated or unheated culture filtrates of selected bacterial strains was used for the detection of their antimicrobial activity against four WDF. It was shown that Streptomyces atratus, S. tsukiyonensis, and Streptomyces sp. greatly inhibited the mycelial growth of the WDF tested compared with the control. To evaluate the biocontrol efficacy of S. atratus, S. tsukiyonensis, and Streptomyces sp., wood blocks of Pinus densiflora inoculated with three selected Streptomyces isolates were tested for weight loss, compression strength (perpendicular or parallel to the grain), bending strength, and chemical component changes. Of these three isolates used, Streptomyces sp. exhibited higher inhibitory activity against WDF, especially G. trabeum, as observed in mechanical and chemical change analyses. Scanning electron microscopy showed that cell walls of the wood block treated with Streptomyces strains were thicker and collapsed to a lesser extent than those of the non-treated control. Taken together, our findings indicate that Streptomyces sp. exhibits the potential to be used as a biocontrol agent for wood decay brown rot fungus that causes severe damage to coniferous woods.